Non-basic azolotriazinone MCHR1 antagonists for the treatment of obesity: An empirical brain-exposures-driven candidate selection for in vivo efficacy studies. Issue 20 (15th October 2015) - Devasthale, Pratik; Wang, Wei; Mignone, James; Renduchintala, Kishore; Radhakrishnan, Sridhar; Dhanapal, Jayanthi; Selvaraj, Jagannath; Kuppusamy, Rajesh; Pelleymounter, Mary Ann; Longhi, Daniel; Huang, Ning; Flynn, Neil; et al.
Graphical abstract: Abstract: Non-basic azolotriazinones were explored using an empirical free brain exposures-driven approach to identify potent MCHR1 antagonists for evaluation in in vivo efficacy studies. An optimized lead from this series, 1j (rMCHR1 K i  = 1.8 nM), demonstrated a 6.9% reduction in weight gain relative to vehicle in a rat model at 30 mg/kg after 4 days of once-daily oral treatment as a glycine prodrug. Despite a promising efficacy profile, an assessment of the biliary toxicity risk of this compound rendered this compound non-progressible.